Schülerauslese, schulische Beurteilung und Schülertests 1880-1980 - Reh, Sabine; Bühler, Patrick; Hofmann, Michèle; Moser, Vera (Bildungsgeschichte. Forschung - Akzente - Perspektiven, 2021)
The way schools deal with "heterogeneity" of pupils has been the subject of a heated debate for a number of years. The present volume shows how the observation of differences between pupils - such as those in aptitude, behaviour and interest - has increasingly come into focus in schools since the last third of the 19th century. Disputes about how "suitable" learning groups should be put together against this background increasingly determined the picture of educational and school-political debates. Selection mechanisms in the school system between 1880 and 1980 are reconstructed that distinguished between the normal and the non-normal, between the gifted and the less gifted, between those who adapted and those who did not. The contributions examine practices of observing, testing and assessing pupils, the procedures and tests used for this purpose, and the individual, pedagogical and political conditions and consequences associated with them.